ANALISA KINERJA MESIN PENCACAH BOTOL PLASTIK TIPE PET - Nuha Desi Anggraeni (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2019)
Plastic waste production in 2015 reached 146 tons per year. This amount is the highest amount of waste compared to other solid waste sectors. The most plastic waste is packaging plastic waste which is often used to package food and beverages. Because of the amount of waste, plastic waste needs to be processed so that it can be reused into other objects. One of the uses of plastic waste is by carrying out plastic counting to be used again. In a previous study, a scissor-type plastic crusher machine was built with a capacity of 50 kg / hour with a diesel engine. The plastic chopper machine needs to be tested for performance to determine the suitability of the results of realization with the initial design. Engine performance tested and analyzed were engine capacity, noise level, crushing efficiency, and machine vibration and crushing quality. The test results show the actual capacity of the engine is 36.68 kg / hour; the efficiency of the crushing results is 73.37%, the noise level when carrying out the crushing is 80.6 dB, the vibration generated when carrying out the crushing is 4.9 mm / s2, and the yield 73.45% crushing.